Relation Between Encapsulation and Adherence Properties of Bacteria Streptococci of Serological Group B to DEAE-Sephacel (HUBUNGAN ANTARA KEBERADAAN KAPSUL DENGAN SIFAT ADHESIFITAS BAKTERI STREPTOKOKUS GRUP B PADA DEAE-SEPHACEL) - Pasaribu, Fachriyan; Wibawan, I Wayan Teguh; Lammler, Christoph (Jurnal Veteriner, 2016)
Abstak dapat dibaca pada Full Text Abstract can be read at Full Text
Keywords: Encapsulation; Adherence Properties; streptococci group B; DEAE-spachel